ELECTRONIC WALL CLOCK WITH LED AND SEVEN SEGMENT POINTER - Indra Yadika Saputra; Drs. Lingga Hermanto, MM (Jurnal Sistem Komputer, 2004)
In making this writing, the author makes a simple tool in the form of an electronic clock display with hours, minutes and seconds are interesting. Two of the seven segment displays double pulses minutes and seconds. While the hours indicated by the LED 12 arranged around the seven segment.The purpose of this paper is to analyze how the workings of the tool, what errors found on the appliance, as well as what components are used in the manufacture of this appliance. At the research / writing, writer use method of book study, namely materials associated with the writing of the book and testing these tools, namely data drawn from experimental results using a simple tool which was then analyzed and explained.In this tool Decade Counter IC used for the calculation of the number of incoming pulses at the input. And used BCD to Decimal Decoder IC that will encode binary information in question into the appropriate voltages to mendrive display devices.